Sustainable food consumption promotion through online marketing communication: The case of Slovenian and Croatian grocery stores - Korez Vide, Romana; Juhart, Sergeja; Hunjet, Anica (Archives of Business Research, 2021)
In this paper we discuss promotion of sustainable food consumption through online marketing communication. In the research we comparatively analyze selected Slovenian and Croatian grocery stores’ webpages from the aspect of the scope and the approaches of sustainable food consumption promotion. We focused on the sustainable/green products in the grocery stores’ sales offers, including products’ packaging, brands and labels, sustainable food products’ related projects, additional informing of consumers about important sustainability topics, placement, and the scope of advertising of sustainable products on the grocery stores’ websites, as well as on the comprehensiveness of communication, reflected also in the provision of sustainability reports. The research findings show that sustainability efforts are visible from the webpages of all analyzed grocery stores, however, the online marketing communication of sustainable food products is most developed in international grocery stores’ chains that are globally present and have more resources at their disposal. We noticed several differences in the scope of sustainable food products sales offers between the observed grocery stores, and in the approaches towards branding, labelling, and providing information about sustainable/green food products. We recognize the importance of institutional support to the awareness rising about the importance of sustainable consumer behaviour for society’s long-term common good. We indicate the COVID-19 pandemic as an important turning point for future orientations of businesses and consumers, particularly in the case of food products. Here, the digital marketing communication can take a leading role in promoting sustainable food consumption.